BIOLOGICAL PRE -TREATMENT USE LOCAL WILD STRAIN OF LIGNOLYTIC FILAMENTOUS BACTERIA TO IMPROVE IN VITRO DRY MATTER DIGESTABILITY AND REDUCTION LIGNIN CONTENT OF LOW QUALITY ROUGHAGES . - & Al-Khateeb, Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study being performed at the central laboratory for graduate students Animal Resources Department / College of Agriculture / University of Baghdad/Aljadrea and in laboratory of applied microbiology Department, Food and Biotechnology Center /Directorate of Agriculture Research / Baghdad, Iraq. Wild strain of local ligninolytic bacteria of genus Streptomyces MS  isolated from Iraq camel degrade feces was used to pre- treated of low quality roughages in in vitro fermentation. Roughages wheat straw (WS), corncobs (Cc), alfalfa hay (AH) was pre- treated with wild strain of genus Streptomyces MS. The results showed higher significant improvement (p